2019
DOI: 10.3390/pharmaceutics11080371
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics of Intravitreal Injections into Liquid Vitreous Substitutes

Abstract: Intravitreal injections have become the cornerstone of retinal care and one of the most commonly performed procedures across all medical specialties. The impact of hydrodynamic forces of intravitreal solutions when injected into vitreous or vitreous substitutes has not been well described. While computational models do exist, they tend to underestimate the starting surface area of an injected bolus of a drug. Here, we report the dispersion profile of a dye bolus (50 µL) injected into different vitreous substit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 48 publications
1
18
0
1
Order By: Relevance
“…Finally, there has been increased interest in the biotransport of the vitreous humor and vitreous substitutes, particularly due to increased clinical use of intravitreal injection to deliver therapeutics. 10,16,18,[168][169][170][171][172][173][174][175][176][177][178][179][180][181][182][183] The motion of fluid inside the vitreous (intact or liquefied) due to eye rotation or saccadic eye movement has been investigated by many groups, 168,169,171,180,183 with particular implications shown for drug delivery and pharmacokinetics in the vitreous. 170,172,173,178,184 A model of enzymatic degradation of the vitreous was created and used to study the mobility of intravitreal nanoparticles, which could better simulate the biotransport of a therapeutic injected into aged and liquefied vitreous.…”
Section: Microscale Factors To Considermentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, there has been increased interest in the biotransport of the vitreous humor and vitreous substitutes, particularly due to increased clinical use of intravitreal injection to deliver therapeutics. 10,16,18,[168][169][170][171][172][173][174][175][176][177][178][179][180][181][182][183] The motion of fluid inside the vitreous (intact or liquefied) due to eye rotation or saccadic eye movement has been investigated by many groups, 168,169,171,180,183 with particular implications shown for drug delivery and pharmacokinetics in the vitreous. 170,172,173,178,184 A model of enzymatic degradation of the vitreous was created and used to study the mobility of intravitreal nanoparticles, which could better simulate the biotransport of a therapeutic injected into aged and liquefied vitreous.…”
Section: Microscale Factors To Considermentioning
confidence: 99%
“…18 An in vitro ocular flow model called the PK-Eye was proposed for use in preclinical drug development, 175 which can allow for testing of therapeutics in vitreous substitutes. 174,181,182 These advances will enable significant progress in determining pharmacokinetics and therapeutic feasibility at earlier stages. However, these advancements are still mostly based on the in vitro properties of the vitreous humor, which likely limits their usefulness and accuracy in in vivo applications.…”
Section: Microscale Factors To Considermentioning
confidence: 99%
“…324 Convection effects has been reported to have a bigger influence to mixing than saccades. 24,[325][326][327][328] A study 329 reported the differences in transport mechanism between human and neonatal mouse eyes. 329 The transport mechanism in the eyes of a mouse was predominantly diffusive.…”
Section: Importance Of Flow In An In Vitro Modelmentioning
confidence: 99%
“…Computer modelling studies have been extensively conducted to understand how a drug is distributed within the vitreous after drug administration. 328 Two common methods of computational modelling of drug distribution recognised by the FDA include Compartmental Modelling (CM) and Finite Element Analysis (FEA). 335,336 CM is a cruder method, where the globe is divided into large segments and rules applied to each one; whereas FEA can map very specific local variations in greater detail.…”
Section: Drug Distribution After Intravitreal Injectionmentioning
confidence: 99%
See 1 more Smart Citation